Isolated Uterine Metastasis of Invasive Ductal Carcinoma - Arslan, Deniz (Hindawi Publishing Corporation, 2013)
Introduction. Most common metastasis sites of breast cancer are the lungs, bones, liver, and brain, whereas uterine involvement by metastatic breast disease is rare. Metastatic carcinoma of the uterus usually originates from other genital sites, most commonly being from the ovaries. Invasive lobular carcinoma spreads to gynecologic organs more frequently than invasive ductal carcinoma. Case Report. A 57-year-old postmenopausal woman was diagnosed with breast carcinoma 2 years ago and modified radical mastectomy was performed. Pathological examination of tumor revealed invasive ductal carcinoma, stage IIIc. She presented with abdominal pain and distension. Diagnostic workup and gynecologic examination revealed lesions that caused diffuse thickening of the uterus wall. Endometrial sampling was performed for confirmation of the diagnosis. She underwent total abdominal hysterectomy and bilateral salpingo-oophorectomy. Breast carcinoma metastases in endometrium and myometrium were confirmed histopathologically and immunohistochemically. Conclusion. We herein report the first case of isolated uterine patient who had invasive ductal carcinoma of breast.